The effect of shared auditors in the supply chain on cost stickiness - Chun Cai; Qianwen Zheng; Lei Zhu (China Journal of Accounting Research, 2019)
Do supply chain audits have real effects? We focus on the effect of shared auditors in the supply chain on corporate cost stickiness. When a supplier shares auditors with its customers, the shared auditors provide informational advantages for suppliers' managers, thus revising their optimistic or pessimistic expectations and influencing suppliers' cost stickiness. Using a sample of Chinese A-share listed companies from 2009 to 2017, we explore the relationship between shared auditors and suppliers' cost stickiness conditional on management expectations. The results show that shared auditors in the supply chain reduce suppliers' cost stickiness significantly when suppliers' managers hold optimistic expectations, and increase suppliers' cost stickiness in cases of pessimistic expectations. Furthermore, the greater the number of shared auditors, the stronger the effect. Such effects are more pronounced when supplier firms share auditors with important customers, have higher demand uncertainty, and use big 10 auditors.
Keywords: 650; Shared auditors; Cost stickiness; Management expectations; Information environment; Supply chain